(untitled) (Journal of the Bangladesh Agricultural University, 2020)
This research was carried out to evaluate the effect of concentrate supplementation on growth, milk yield and composition, and reproductive responses of crossbred Zebu cows for 120 days (two months pre-partum and two months post-partum). Six (06) advanced pregnant (60 days of pre-partum) crossbred Zebu cows in second parity were equally divided into two groups like control and supplemented. About 22.0 kg mixed green fodders (Para: German =2:1) and 2.0 kg concentrate mixtures (wheat bran, mustard oil cake, common salt and di-calcium phosphate were 82.28, 13.72, 3.70 and 0.30%, respectively) were offered as basal diet to each cow of both groups. Besides these, an extra amount (0.5 kg) of concentrate mixture (wheat bran- 50%, mustard oil cake- 40%, common salt[1]2% and di-calcium phosphate- 8%) was supplied to each cow of supplemented group. Results revealed that pre-and post-partum dry matter intake was significantly (p=0.000) higher in the supplemented group compared to the control group but concentrate supplementation did not affect on body weight and body condition score of the zebu cows. About 19% of milk production was increased (p=0.000) due to concentrate supplementation in the diet of crossbred zebu cows but milk composition remained unchanged (p>0.05). On the other hand, the birth weight of calves was non-significantly (p=0.29) higher (24%) in additional concentrate supplementation group compared to the control group. Moreover, it was found that a limited amount of concentrate supplementation was able to reduce about 12 days of post-partum heat period (p=0.02) and days open (p=0.01) of Zebu cows which would be helpful to gear up the tropical dairy animal production. It is concluded that supplying an additional amount of concentrate to the cows before and after 2 months of freshening had a positive influence on milk production as well as reproductive performance. J Bangladesh Agril Univ 18(1): 117–123, 2020 https://doi.org/10.5455/JBAU.94751